Do privacy concerns determine online information disclosure? The case of internet addiction. (5th April 2021) - Thompson, Nik; Ahmad, Atif; Maynard, Sean
Abstract : Purpose: It is a widely held belief that users make a rational cost-benefit decision when choosing whether to disclose information online. Yet, in the privacy context, the evidence is far from conclusive suggesting that strong and as-yet unmeasured influences on behaviour may exist. This paper aims to demonstrate one such link – the effect of internet addiction on information disclosure. Design/methodology/approach: Data from 216 Web users was collected regarding their perceptions on privacy and information disclosure intentions as well as avoidance behaviour, an element of internet addiction. Using a research model based on the Privacy Calculus theory, structural equation modelling was applied to quantify the determinants of online disclosure under various conditions. Findings: The authors show that not all aspects of privacy (a multi-dimensional construct) influence information disclosure. While concerns about data collection influence self-disclosure behaviour, the level of awareness about privacy does not. They next examine the impact of internet addiction on these relationships, finding that internet addiction weakens the influence of privacy concerns to the point of non-significance. Originality/value: The authors highlight some of the influences of self-disclosure behaviour, showing that some but not all aspects of privacy are influential. They also demonstrate that there are powerful influences on user behaviour that have not been accounted for in prior work; internet addiction is one of these factors. This provides some of the first evidence of the potentially deleterious effect of internet addiction on the privacy calculus.